plz answer it
the best answer will be marked as brainliest answer
Attachments:
![](https://hi-static.z-dn.net/files/da6/129a9b6a2dd9360e5f54899c57efa502.jpg)
Answers
Answered by
0
we know ,
a³ + b³ + c³ -3abc = (a + b + c )(a² + b² + c² -ab -bc-ca)
now ,
a + b + c = 5
ab + bc + ca = 10
(a + b + c)² = a² + b² + c² +2(ab + bc+ca)
(5)² -2×10 = a² + b² + c²
a² + b² + c² =5
hence ,
a³ + b³ +c³ -3abc = ( a + b + c )(a² + b² + c² -ab- bc-ca)
=( 5)( 5 - 10) = 5 × (-5) = -25
mark as brainliest !
Answered by
0
Answer:
hope its help you
please add me in brainlist
Attachments:
![](https://hi-static.z-dn.net/files/da8/edfa417d02b8a84216a645556604b0be.jpg)
Similar questions
Math,
6 months ago
Math,
6 months ago
Math,
6 months ago
Math,
1 year ago
Business Studies,
1 year ago
Science,
1 year ago
Social Sciences,
1 year ago